Pregled metod za optimizacijo procesa liofilizacije in vrednotenje liofilizatov - Pečnik, Matija (Farmacevtski vestnik, 2024)
Due to the increasing complexity of new active substances, lyophilisation or freeze-drying is a commonly used processing method especially for the production of parenteral dosage forms.It also enables the production of medicines that are adapted for the individual patient needs in terms of application, especially oral lyophilisates for children and elderly or patients with certain psychiatric disorders. The principle of Quality by Design in the development and production of lyophilisates creates the need for reliable methods to evaluate critical quality parameters of medicines and critical attributes of starting materials. This article reviews the most common and innovative methods for the evaluation of critical in-process material attributes and critical quality attributes used during optimisation of process parameters and formulation composition.
Keywords: Farmacevtske oblike; liofilizacija; metode; predformulacija